(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Udhruh Fortress in southern Jordan was constructed in AD 303–304 by the Roman Legionis VI Ferratae as part of the Limes Arabicus to serve as a stronghold against desert nomads. Recent excavations within the fortress have unearthed several unstratified skeletal remains, raising questions about their identity and origin. To address this, we conducted 87Sr/86Sr analysis on dental enamel from 10 individuals to determine their potential mobility, which mirrors the origin of ingested food during childhood and thus the geological region where individuals spent their early years. To establish a bioavailable strontium ratio for Udhruh fortress, we considered the published 87Sr/86Sr ratios from three sites near Udhruh, specifically Basta, Khirbet Nawafleh, and Dajaniah. All the reported strontium data were corrected against the NIST SRM987 standard by Wang and colleagues. The results of the study showed no migrations into the study area and showed a high probability of mobility between fortresses and/or sites in the study area. In other words, the sampled individuals were mostly Roman local legionnaires, thus supporting the notion that the identity of being "Roman" was linked to the formidable might and authority of the Roman state rather than cultural characteristics.